2015
DOI: 10.1021/ac503627z
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Spatial Analysis of the Mouse Brain Lipidome by Pressurized Liquid Extraction Surface Analysis

Abstract: Here we describe a novel surface sampling technique termed pressurized liquid extraction surface analysis (PLESA), which in combination with a dedicated high-resolution shotgun lipidomics routine enables both quantification and in-depth structural characterization of molecular lipid species extracted directly from tissue sections. PLESA uses a sealed and pressurized sampling probe that enables the use of chloroform-containing extraction solvents for efficient in situ lipid microextraction with a spatial resolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(79 citation statements)
references
References 47 publications
(66 reference statements)
1
77
1
Order By: Relevance
“…A number of groups have limited the spreading of the probe solvent by using electrodes 5 or applying pressure on top of the solvent. 4 Another way of limiting solvent spread is contact LESA 6 or performing laser ablation rather than liquid extraction. 7 It already has been observed that the spreading of the extraction solvent on hydrophilic surfaces is substantial 6 and that the use of nonpolar solvents such as chloroform dramatically increases the solvent spread.…”
Section: * S Supporting Informationmentioning
confidence: 99%
“…A number of groups have limited the spreading of the probe solvent by using electrodes 5 or applying pressure on top of the solvent. 4 Another way of limiting solvent spread is contact LESA 6 or performing laser ablation rather than liquid extraction. 7 It already has been observed that the spreading of the extraction solvent on hydrophilic surfaces is substantial 6 and that the use of nonpolar solvents such as chloroform dramatically increases the solvent spread.…”
Section: * S Supporting Informationmentioning
confidence: 99%
“…84 Such “contact” model LESA may be advantageous for the analysis of samples containing a protective layer on the surface. When installed on a fully automated robotic system, it enables high-throughput, spatially resolved analysis of metabolites, 85,86 lipids, 8790 and proteins 91,92 in complex samples, including dried blood spots, 84,88 contact lenses, 89 tissues, 55,83,86,91 and microbial colonies. 84,93 LESA also has been used for analyzing molecules separated using TLC 83 and capillary electrophoresis.…”
Section: Ambient Liquid Extraction Techniquesmentioning
confidence: 99%
“…87 In PLESA experiments, a pipet filled with ~500 nL of organic extraction solvent is pressed into the sample, forming a sealed microextraction volume. Improved extraction efficiency is achieved by applying headspace pressure to the pipet during the ~30 s extraction time.…”
Section: Ambient Liquid Extraction Techniquesmentioning
confidence: 99%
See 2 more Smart Citations